2013
DOI: 10.3109/00016489.2012.757798
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular compensation after vestibular schwannoma surgery: normalization of the subjective visual vertical and disability

Abstract: Patients with lesser degrees of caloric weakness took longer to normalize SVV than those with a higher caloric weakness before surgery (p < 0.05). There was a significant correlation between DHI and improvements in SVV with time. The differences disappeared in 6 months where all patients, with greater or lesser degree of caloric weakness, had the same results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…The recovery from SVV tilt after an acute vestibular deficit (neurotomy, vestibular schwannoma surgery, and neuritis) has already been described [Vibert and Häusler, 2000;Lopez et al, 2007;Batuecas-Caletrio et al, 2013]. In these studies, the SVV values gradually normalized after 6-12 months, long after the disappearance of the vertigo.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The recovery from SVV tilt after an acute vestibular deficit (neurotomy, vestibular schwannoma surgery, and neuritis) has already been described [Vibert and Häusler, 2000;Lopez et al, 2007;Batuecas-Caletrio et al, 2013]. In these studies, the SVV values gradually normalized after 6-12 months, long after the disappearance of the vertigo.…”
Section: Discussionmentioning
confidence: 64%
“…In these studies, the SVV values gradually normalized after 6-12 months, long after the disappearance of the vertigo. It was previously reported that in patients with a temporoparietal stroke or a vestibular neurotomy, a tilted SVV appears to be related to persistent vestibular symptoms [Min et al, 2007;Batuecas-Caletrio et al, 2013]. Indeed, visually guided movements such as those used in SVV evaluation implicate the transformation of a position in space to coordinates related to a body-centered reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two other investigations showed that only 40% to 60% of elderly patients with confirmed BPPV reported vertiginous symptoms compared with 90% of young adult patients with BPPV (21,23). Instead of vertigo, elderly patients with BPPV more frequently reported unsteadiness and imbalance.…”
Section: Discussionmentioning
confidence: 94%
“…This faster compensation has been measured with different objective tests such as subjective visual vertical or computerized dynamic posturography and semiquantitative measures such as the Dizziness Handicap Inventory (18). …”
Section: Introductionmentioning
confidence: 99%